Development of E-Modules with Online Tests to Increase Students' Motivation and Learning Outcomes in Class XI - Anggraini, Syafrida; Armiati, Armiati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to develop an e-module learning media that contains online tests on the subject of Accounting Practicum in Service, Trade, and Manufacturing Companies for class XI Accounting. The method used is Research and Development using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). Data collection techniques used interviews, questionnaires, and assessment of student learning outcomes in the form of tests. The data analysis technique used is quantitative descriptive. To find out the impact of e-module learning media containing online tests, an analysis was carried out by testing the hypothesis. The results showed that the development of e-modules containing online tests met the valid, practical, and effective criteria to increase student motivation and learning outcomes. The validation results from the experts stated that the e-module learning media containing online tests was valid with a valid assessment category. The practicality test conducted with teacher and student respondents showed that the e-module learning media containing online tests was practical to use. The results of testing the effectiveness of e-module learning media containing online tests showed a significant difference between the motivation and learning outcomes of students who studied using e-module learning media containing online tests and students who studied without using e-module learning media containing online tests.